A multimodalidade em contextos de negação nas interações mãe-bebê - Almeida, Laís Cavalcanti de (2018)
From a very early age, denial appears in interaction scenes between children and adults, through crying, body / facial expression, looking, gestures and speech. Taking this proposition as a starting point, we aim in this research: analyse the denial expressions inside the mother-baby interactional context from the multimodal perspective in language acquisition. The present report relates gestures and speech from the classification of multimodality, that is, as a single meaning matrix. In this study perspective, we dialog with the following authors: McNeill (1985); Cavalcante (1994); Barros (2012); Soares (2014); Dodane & Massini-Cagliari (2010); Spitz (1998); Beaupoil-Hourdel (2013); Andrén (2014), Vasconcelos (2017) and Barros & Fonte (2016). To achieve the proposed goal, we analyzed data from a mother-baby dyad through video recordings of interactive and naturalistic situations of a mother with her daughter, the data were made available by the LAFE - LAFE – Laboratório de Aquisição da Fala e da Escrita and transcribed by the ELAN software, and it is a longitudinal case study that accompanied a child aged 1 to 24 months. Observing the interaction scenes between the dyad, we verify, through the baby part several contexts of denials marked throughout the life time, and we classify them, as: dissatisfaction, rejection, refusal, evasion and prohibition. We obtained as a result that denial is one of the first clues that mark the child's position/imposition within the interaction. In the first 3 months, the mother is the protagonist of the interaction scenes. During this period, the child expresses himself by dissatisfaction and rejection through crying. The mother understands crying as denial, a way for the child to make a stand when he is hungry, with a dirty diaper, uncomfortable with the position, among other meanings established by the mother. At 6 months, dissatisfaction does not appear merely physiological as before, as the child recognizes itself as an interactive partner and imposes itself when dissatisfied. From 12 months on, the child uses all multimodal devices to demonstrate denial within interactions. We realize that denial expressions are present in almost all moments of the mother-baby interaction, both the mother and the child produce these expressions. We believe that is of a great importance stimulating and carrying out expressions by the mother within the interactions, because it is through the movements and vocal production performed by the mother that the child begins its first steps in the construction of the continuous gestuo-vocal. We conclude by corroborating the importance of denials as an expressive form of the child in the interaction, since they are the first elements that the child uses to show his opinion and statement within the interaction. A way to consolidate the mother-child relationship.